Activity of murine surrogate antibodies for durvalumab and tremelimumab lacking effector function and the ability to deplete regulatory T cells in mouse models of cancer. Issue 1 (1st January 2021) - Schofield, Darren J.; Percival-Alwyn, Jennifer; Rytelewski, Mateusz; Hood, John; Rothstein, Raymond; Wetzel, Leslie; McGlinchey, Kelly; Adjei, Grace; Watkins, Amanda; Machiesky, LeeAnn; Chen, Weimin; Andrews, John; et al.
ABSTRACT: Preclinical studies of PD-L1 and CTLA-4 blockade have relied heavily on mouse syngeneic tumor models with intact immune systems, which facilitate dissection of immunosuppressive mechanisms in the tumor microenvironment. Commercially developed monoclonal antibodies (mAbs) targeting human PD-L1, PD-1, and CTLA-4 may not demonstrate cross-reactive binding to their mouse orthologs, and surrogate anti-mouse antibodies are often used in their place to inhibit these immune checkpoints. In each case, multiple choices exist for surrogate antibodies, which differ with respect to species of origin, affinity, and effector function. To develop relevant murine surrogate antibodies for the anti-human PD-L1 mAb durvalumab and the anti-human CTLA-4 mAb tremelimumab, rat/mouse chimeric or fully murine mAbs engineered for reduced effector function were developed and compared with durvalumab and tremelimumab. Characterization included determination of target affinity, in vivo effector function, pharmacokinetic profile, and anti-tumor efficacy in mouse syngeneic tumor models. Results showed that anti–PD-L1 and anti–CTLA-4 murine surrogates with pharmacologic properties similar to those of durvalumab and tremelimumab demonstrated anti-tumor activity in a subset of commonly used mouse syngeneic tumor models. This activity was not entirely dependent on antibody-dependent cellular cytotoxicity, antibody-dependent cellular phagocytosis effector function, or regulatory T-cell depletion, as antibodies engineered to lack these features showed activity in models historically sensitive to checkpoint inhibition, albeit at a significantly lower level than antibodies with intact effector function.